Mechanisms of traditional Chinese medicine overcoming of radiotherapy resistance in breast cancer - Zhao, Xiaohui; Luo, Ting; Qiu, Yuting; Yang, Zhiwei; Wang, Danni; Wang, Zairui; Zeng, Jiale; Bi, Zhuofei (Frontiers in Oncology, 2024)
Breast cancer stands as the most prevalent malignancy among women, with radiotherapy serving as a primary treatment modality. Despite radiotherapy, a subset of breast cancer patients experiences local recurrence, attributed to the intrinsic resistance of tumors to radiation. Therefore, there is a compelling need to explore novel approaches that can enhance cytotoxic effects through alternative mechanisms. Traditional Chinese Medicine (TCM) and its active constituents exhibit diverse pharmacological actions, including anti-tumor effects, offering extensive possibilities to identify effective components capable of overcoming radiotherapy resistance. This review delineates the mechanisms underlying radiotherapy resistance in breast cancer, along with potential candidate Chinese herbal medicines that may sensitize breast cancer cells to radiotherapy. The exploration of such herbal interventions holds promise for improving therapeutic outcomes in the context of breast cancer radiotherapy resistance.